The prevalence and risk factors of musculoskeletal disorders among Indonesian dental professionals - Kholinne, Erica; Azalia, Xarisa; Rahayu, Erika Putri; Anestessia, Ira Juliet; Agil, Nadifa; Muchtar, (Frontiers in Rehabilitation Sciences, 2025)
Dental professionals (DPs) are at significant risk of developing work-related musculoskeletal disorders (WMSDs). This study aimed to determine the prevalence of WMSDs among DPs and identify associated factors based on professional level. A cross-sectional analysis was conducted on 151 dental professionals, including dentists, dental nurses, and dental assistants, from various universities and health institutes in Indonesia. Data were collected using the Nordic Musculoskeletal Questionnaire. Associations between WMSD symptoms and qualitative data (demographics, job characteristics, and other factors) were examined using the Chi-square test, while quantitative data were analyzed using the independent t-test. The results showed that 96% of respondents (145 out of 151) had experienced WMSDs, with the back (68.2%), waist (66.9%), upper neck (60.9%), and lower neck (59.6%) being the most commonly affected regions. Muscle fatigue (53.6%) and pain (49.7%) were the most frequently reported symptoms. Triggering factors included unergonomic body posture (84.1%) and prolonged sitting (53.6%), while protective factors included rest (71.5%) and improved body posture (53%). Physical exercise was significantly associated with WMSDs (p < 0.001). This study highlights the high prevalence of WMSDs among dental professionals and underscores the need for ergonomic training, physical exercise, and equipment modification to mitigate these conditions. Limitations of the study include unequal distribution among professional groups and a gender imbalance, which may affect the generalisability of the findings.